2012
DOI: 10.1002/aur.1256
|View full text |Cite
|
Sign up to set email alerts
|

Autism Risk Gene MET Variation and Cortical Thickness in Typically Developing Children and Adolescents

Abstract: MET receptor tyrosine kinase (MET) has been proposed as a candidate risk gene for autism spectrum disorder (ASD) based on associations between MET polymorphisms and ASD diagnosis, as well as evidence from animal studies that MET protein may regulate early development of cortical regions implicated in the neurobiology of ASD. The relevance of differences in MET signaling for human cortical development remains unexamined, however. We sought to address this issue by relating genotype at a functional single nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 38 publications
3
31
0
Order By: Relevance
“…In contrast, MET signaling appears to have no impact on proliferation or survival in the developing telencephalon (Judson et al, 2010). Rather, accumulating evidence from morphological and electrophysiological studies in genetically manipulated animal models and from human imaging studies indicates that, in the cortex, MET signaling influences circuit maturation (Qiu et al, 2011; Hedrick et al, 2012; Qiu et al, 2014). The present study, together with previous analyses examining effects of MET activation (Gutierrez et al, 2004; Tyndall and Walikonis, 2006; Nakano et al, 2007; Lim and Walikonis, 2008; Judson et al, 2010; Finsterwald and Martin, 2011; Qiu et al, 2011; Qiu et al, 2014), suggest that the results from both human and animal models in vivo are likely due to MET’s effects on dendritic and spine morphogenesis, and synapse development.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, MET signaling appears to have no impact on proliferation or survival in the developing telencephalon (Judson et al, 2010). Rather, accumulating evidence from morphological and electrophysiological studies in genetically manipulated animal models and from human imaging studies indicates that, in the cortex, MET signaling influences circuit maturation (Qiu et al, 2011; Hedrick et al, 2012; Qiu et al, 2014). The present study, together with previous analyses examining effects of MET activation (Gutierrez et al, 2004; Tyndall and Walikonis, 2006; Nakano et al, 2007; Lim and Walikonis, 2008; Judson et al, 2010; Finsterwald and Martin, 2011; Qiu et al, 2011; Qiu et al, 2014), suggest that the results from both human and animal models in vivo are likely due to MET’s effects on dendritic and spine morphogenesis, and synapse development.…”
Section: Discussionmentioning
confidence: 99%
“…Using a conditional transgenic (Cre-LoxP) approach, the loss of the signaling domain of Met in GABAergic interneurons and dorsal striatum impaired goal-directed learning (Martins et al, 2011). Loss of Met signaling in the mouse cerebral cortex [using the floxed Met mouse (Met-fx) with the cerebral cortical and hippocampal specific Emx1-cre mouse, denoted as the Met-Emx1 mouse] yielded anatomical changes (Smith et al, 2012) similar to those reported in individuals with the autism-associated "C" risk allele of MET (Hedrick et al, 2012). In the current study, we used an in vitro thalamocortical slice preparation of wild-type (WT) and MetEmx1 littermates to reveal cellular mechanisms underlying sensory deficits related to ASD.…”
Section: Introductionmentioning
confidence: 95%
“…To date, neuroimaging-genetics studies have taken two forms: studies of the effects of ASD-associated risk alleles on brain measures in neurotypical children, adolescents, and adults (eg, Clemm von Hohenberg et al, 2013; Dennis et al, Hedrick et al, 2012;Raznahan et al, 2012;Sauer et al, 2012;Tan et al, 2010;Voineskos et al, 2011;Whalley et al, 2011) and studies comparing the effects of ASD-associated risk alleles on children and adolescents with ASD compared with neurotypical controls (eg, Rudie et al, 2012a;. investigated the impact of the contactin-associated protein-like 2 (CNTNAP2) rs2710102, C risk allele on functional connectivity in children and adolescents with ASD.…”
Section: Integrating Imaging and Geneticsmentioning
confidence: 99%